Unveiling post-MIS-N cardiomyopathy by longitudinal multimodality global cardiac assessment from neonatal insult to 16-month follow-up - Maitri Chaudhuri; Munesh Tomar; Balasubramanyam Shankar (Annals of Pediatric Cardiology, 2023)
A full-term male neonate presented on the 11th day of life with late-onset multisystem inflammatory syndrome-neonate (MIS-N) (cardioneurological compromise). Immediate anti-inflammatory modulation led to a gradual recovery of neurological and coronary lesions. However, temporal evaluation unmasked silent myocardial dysfunction in echocardiography validated further by elevated biomarkers, myocardial fibrosis in cardiac magnetic resonance imaging, and abnormal strain study persisting till 16 months of follow-up. This revealed a hitherto unknown and rare progression of MIS-N into dilated cardiomyopathy.